Monitoring the Event-Building Features of the ATLAS RPCs ROD With an Embedded Microprocessor - Aloisio, A.; Capasso, L.; Cevenini, F.; Pietra, M. Della; Izzo, V. (IEEE transactions on nuclear science, 2010)
The readout data of ATLAS' resistive plate chamber muon spectrometer are collected by the front-end electronics and transferred via optical fibers to the readout driver (ROD) boards in the counting room. Each ROD arranges all the data fragments of one sector of the spectrometer in a unique event. This is made by the Event Builder logic, a cluster of finite state machines that parses the fragments, checks their syntax, and builds an event containing all the sector data. In this paper, we describe the Builder Monitor, developed to analyze the Event Builder timing performance. It is designed around a 32-bit soft-core microprocessor embedded in the same field-programmable gate array hosting the Event Builder logic. This approach makes it possible to track the algorithm execution. The monitor performs real-time and statistical analysis of the state machine dynamics. The microprocessor is interfaced with custom peripherals, which read out the state registers and fill histograms and transfer them via direct memory access to the processor memory. The Builder Monitor also measures the elapsed time for each event and its length, and keeps track of status words and errors.